Healthcare record management with blockchain technology - Chew, Jia Lun (2022)
This project is a Healthcare record management with blockchain technology for academic purposes. Health is always a major priority and concern in everyone’s lives. Recently, people have started to prioritize their health even more due to the hit of the Covid-19 pandemic. More people are consciously starting to reflect on the importance of having a healthy body instead of chasing materialistic items in their lives. To maintain a healthy body, going for a medical check-up once every few months will be the first step. The test result will alert you on whether you have been diagnosed with any disease, or any unhealthy signs have come up lately. Early detection is key to successfully curing the disease. The medical information retrieved from each medical check-up appointment will be stored in Electronic Health Record (EHR). Although storing healthcare data in EHR brings a lot of benefits, there is still some downside to the current EHR. For example, the security that the current EHR is vulnerable to data breach attack. Many healthcare data have been breached and leaked to the internet throughout the years. Healthcare data is sensitive info that belongs to the patient him/herself. The purpose of this project is to allow patients to have their healthcare data safely stored in the blockchain network which blockchain will provide more robust security due to its unique characteristics such as immutable and transparency. The adopted methodology for this project will be the Prototype model. This methodology will allow the project to be refined and developed based on user feedback. This paper consists of some system flow diagrams that demonstrate how the overall project will work. This paper also discusses a few relevant literature reviews, research analysis, research findings, and the conclusion of this study.